Impact of COVID-19 on people living with HIV and HIV care: A qualitative study in the Volta Region of Ghana. - David Ayangba Asakitogum; Jerry John Nutor; Rachel G A Thompson; Robert K Alhassan; Akua O Gyamerah (Public Library of Science (PLoS), 2024)
The COVID-19 pandemic caused significant social changes and challenges globally, including economic slowdown and limitation of essential services. Our study explored the impact of the COVID-19 pandemic on the HIV treatment experiences and lives of people living with HIV in Ghana. Between October 2021 and January 2022, we conducted four focus group discussions with 24 people living with HIV and six in-depth interviews with healthcare providers to understand the impact of the COVID-19 epidemic on their lives and HIV treatment and care. Transcribed interviews were analyzed using thematic analysis. The COVID-19 pandemic most impacted people living with HIV economically and psychosocially. Economic challenges included loss of income/economic support, financial hardship, and material insecurities. The psychosocial impact included fear of the health impact of COVID-19 on people living with HIV and social isolation. The pandemic also impacted participants' HIV treatment and care services including change in their site of care and non-adherence to antiretroviral therapy. Clinics in particular modified HIV care services to maintain treatment and care during the pandemic. Healthcare providers also implemented direct antiretroviral therapy service delivery to clients, which reduced patient overcrowding but increased providers' workload and expenses. The COVID-19 pandemic caused economic hardship, social isolation, and changes in HIV treatment and care services for people living with HIV. It also imposed a work and financial burden on healthcare providers. However, service changes made by providers helped sustain HIV care and treatment for clients and should inform future pandemic responses in HIV services.